Reflections on factors affecting trading - Sequeira, Byron (Cultura de Paz, 2015)
Negotiation as a method of alternative conflict resolution expresses the practical utility of the culture of peace. The power of word is confirmed, and therefore dialogue is the best expression of this. Sometimes, this form tends to be stigmatized and avoided due to the existence of certain prejudices that are a result of social constructions. However, experience has taught us that while we apply some recommendations in regard to the development of the subject before and during the negotiation, the chances of achieving an agreement increase. DOI: http://dx.doi.org/10.5377/cultura.v20i64.1873 Cultura de Paz Vol.20 Num.64 2015: 17-20